'Children's rights': using digital storytelling and visible thinking approaches to create a narrative video in the early childhood classroom. (2015) - Melliou, Kiriaki; Moutafidou, Anna; Bratitsis, Tharrenos
This study aspires to highlight the use of digital storytelling and visible thinking routines as a means for uncovering young students' ideas of human rights and communicating them effectively to a broad audience. Students of a public kindergarten in a low-income district of Piraeus were encouraged to use several thinking routines to explore the rights that they consider essential for all children's well-being and promote them through the process of creating a digital narrative video. Research findings revealed that the integration of thinking routines into the process of digital storytelling helped students to construct a new identity of themselves as active members of a universal community which respects children's rights in everyday life. The study also highlights the role of technology in motivating young students to express and share their perspectives with an audience beyond their classroom borders, interested in their message.